Analisis Peran Pancasila dalam Pembentukan Norma Hukum Nasional - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Amy Nur Azizah; Marta Pangestuti; Khairina Salsabila Pramono (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This study aims to analyze the role of Pancasila in the formation of national legal norms in Indonesia. As the state ideology, Pancasila influences every aspect of legal development and implementation through the fundamental principles embodied in its five precepts. This research employs a qualitative approach using case studies, document analysis, and interviews to identify how Pancasila's values are integrated into the legal system. Data were collected from legal documents, judicial decisions, and interviews with legal experts and lawmakers. The findings reveal that Pancasila serves as a source of values and normative guidance, ensuring legal consistency, and facilitating evaluation and social control. The study also highlights how Pancasila supports public participation in the legislative process, contributing to a legal system that aligns with national ideals of social justice and democracy. These insights aim to deepen the understanding of how Pancasila’s values are applied withiystem.